Asoociation between “Book of Lamentations” by Grigor Narekatsi and Byzantine Mystic Literature - Dolukhanyan, Aelita (Armenian Folia Anglistika, 2007)
There are striking similarities between the Book of Lamentations by Grigor Narekatsi, the ingenius poet of the 10th century and the hymns by the 11th century Byzantine mystic writer Symeon the New Theologian. The article points out the similarities and states that Grigor Narekatsi could not have used the ideas of Symeon the New Theologian. The two poets composed separately from each other presenting the highest level of Christian mystic thinking. The author of the article, based on the interpretation of the symbols preserved in Manuscript N 7703 of the Matenadaran comes up with a new interpretation of the last stanza of Grogor Narekatsi’s Canto to Vardavar.